CYBERSECURITY IN UZBEKISTAN: PROTECTING THE DIGITAL ECONOMY (International Journal of Economic Integration and Regional Competitiveness, 2024)
Strong cybersecurity standards are more vital than ever as Uzbekistan's digital economy continues to flourish. This article examines the current state of the country's cybersecurity infrastructure, identifying significant risks and flaws that affect both individuals and businesses. It also underlines how the public and private sectors have collaborated to strengthen cybersecurity and create a safe online environment that fosters growth and innovation. By evaluating these components, we may gain a comprehensive understanding of the challenges and preventative measures driving Uzbekistan's strategy for safeguarding its constantly increasing digital environment